Tony Bennett an American classic - Bennett, Tony 1926-2023; Streisand, Barbra 1942-; Legend, John 1978-; lang, k. d. 1961-; Botti, Chris 1962-; Krall, Diana 1964-; Juanes 1972-; John, Elton 1947-; Bublé, Michael 1975-; Wonder, Stevie 1950-; Aguilera, Christina 1980- (Sony BMG Music Entertainment, 2006)
A variety show re-creating the seminal venues of Tony Bennett's career